RESPON PERTUMBUHAN DAN PERKEMBANGAN SAYUR PELENG (Spinacia oleracea) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR PADA BERBAGAI MULSA - Marpaung, Robert G.; Pasaribu, Boy (JURNAL DARMA AGUNG, 2020)
This study aims at determing the response of growth and production of peleng vegetables to the application of liquid organic fertilizer in various mulch. The study was conducted on land located in Simalingkar A Medan with a height of Â± 32 m above sea level, began from May to August 2017. The research method used a factorial randomized block design with 2 factors. The first factor is the dose of NASA liquid organic fertilizer (P) which consists of 3 levels of treatment, namely: P0 = control, P1 = 3 ml / l water and P2 = 6 ml / l water. The second factor is the provision of mulch (M) which consists of three types, namely: M0: without mulching, M1: rice straw mulch and M2: black silver plastic mulch (MPHP). The results showed that the treatment of NASA liquid organic fertilizer up to 6 ml / l water significantly increased plant height, number of leaves, fresh weight of plants per sample, fresh weight of plants per plot, dry weight of plants per sample and dry weight of plants per plot, but differed not markedly on the relative growth rate of plants. The treatment of organic mulch and black silver mulch significantly increased plant height, number of leaves, fresh weight of plants per sample, fresh weight of plants per plot, dry weight of plants per sample and dry weight of plants per plot, but not significantly different to the relative growth rate of plants. The interaction between NASA's liquid organic fertilizer treatment and mulch administration had no significant effect on plant height, number of leaves, plant fresh weight per sample, plant fresh weight per plot, plant dry weight per sample, plant dry weight per plot and relative plant growth rate